NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIA Early experience in clinical use of mechanical ventricular assist Levitronix® device - Pawlak, Szymon; Śliwka, Joanna; Przybylski, Roman; Grzybowski, Adam; Pacholewicz, Jerzy; Urbańska, Ewa; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
The authors present the first two cases of implantation of mechanical circulatory support with Levitronix® CentriMag in Poland. The aim of this study was to assess early results of short-term use of mechanical circulatory support with Levitronix® CentriMag. The first patient was a 4-year-old child, weight only 10 kilograms, with restrictive cardiomyopathy waiting for heart transplantation. Within 21 days the child’s condition had gradually improved and normalization of biochemical parameters was achieved. The second patient was a 57-year-old male, with right ventricle dysfunction. The procedure was performed within the first 24 hours after heart transplantation. In this patient, implantation of mechanical circulatory support allowed ventricle function to be restored, enabled compensation of biochemical parameters and the explantation of the system after 13 days.